Pengaruh Digital Marketing, Electronic Word of Mouth, dan Brand Image Terhadap Purchase Decision (Studi Kasus Bebek Carok di Kota Malang) - Findriani, Nisa Norma; Asiyah, Siti; Amin, Muhammad Sirojuddin (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This research aims to analyze the influence of the Marketing Strategy of Digital Marketing (X1), Electronic Word of Mouth (X2), and Brand Image (X3) on Purchase Decision, partially. That The research method used is a quantitative approach. The sample for this research was of 75 consumers from Bebek Carok who used Bebek Carok products in the city of Malang from a population whose exact number is unknown. Questionnaires were used as a data collection instrument, Validity Test and Reliability Test are used to measure instrument performance. Not only that, this research also uses the Normality Test, Multicollinearity Test, Heteroscedasticity Test, Multiple Linear Regression Analysis, Adjusted R Square Test, and t Test. The results of this research show that digital marketing, electronic word of mouth, and brand image partially have a positive effect and has a significant effect on purchase decisions. Keywords: Digital Marketing, Electronic Word of Mouth, Brand Image, Purchase Decision.